UACA: Unified Access Control Approach For Heterogeneous Database Based-on Service Data Object - Hussein, Sadoon; Maan, Nadia (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Abstract: The requirement for data interchange, access, and retrieval from diverse databases. This requirement is getting more and more crucial. However, retrieving this data from a heterogeneous database necessitates juggling many kinds of query languages, data models, and structure. The goal of this project is to create a unified access control approach (UACA), which will be managed by service data object (SDO) technologies and will be based on an agent mechanism for application access to business databases. To create a unified data access control, applications must be submitted through a UACA. To prevent a direct link to the database and application security threats, unified access control isolates applications from databases. Application systems submit a request for identity authentication to the database access control system using the data access protocol of the access control system. Data are finally transmitted to the application system after identity authentication, data gathering, and data transmission. This investigation led to the creation of a client-middle layer, which is also in charge of transformation and optimization, to ensure uniform data access control and access to the heterogeneous database. It also manages system communication using the TCP/IP protocol to guarantee the accuracy and reliability of the connection. SDO data retrieval offers strong adaptability and system compatibility.